The high‐pressure viscosity of refrigerant/oil systems. (1st February 2017) - Bair, Scott; Baker, Mark; Pallister, David M.
Abstract: Application of the new quantitative elastohydrodynamics to the concentrated contacts operating within refrigerant compressors will require the accurate description of the viscosity of the lubricant that is diluted by the refrigerant. This article presents extensive viscosity measurements on polyolester and polyvinylether oils and their mixtures with low mass fractions (2–23%) of refrigerants R134a and R410a. Pressures up to 400 MPa and temperatures to 100°C were reached. Correlations are presented to predict the viscosity and pressure–viscosity coefficients at arbitrary temperatures and pressures and concentrations. Pressure–viscosity coefficients are compared with those derived from film thickness measurements using one of the popular definitions for the coefficient. Where comparisons can be made, the film‐derived pressure–viscosity coefficients were mostly inaccurate. Part of the problem has been the lack of a single well‐accepted and rigorous definition of the pressure–viscosity coefficient and the lack of an accurate film thickness formula that employs that definition. Copyright © 2017 John Wiley & Sons, Ltd.